HUBUNGAN KARAKTERISTIK IBU HAMIL DAN PELVIC GIRDLE PAIN - Teuku Radja Miftahul Sidqi; Rully Ayu Nirmalasari Haryadi Putri (Fakultas Kedokteran Universitas Trisakti, 2024)
BACKGROUND: Pelvic Girdle Pain is pain that occurs in the posterior area of the pelvis, distal and lateral side of the fifth lumbar vertebra, or at the level of symphysis pubis. Women usually experience this during pregnancy, with a prevalence 14-25%. Pelvic Girdle Pain is provoked by daily activities such as walking, standing, sitting and lying down. It limits almost all ability to perform those tasks. This study aims to determine the relationship between the characteristics of pregnant women and Pelvic Girdle pain. METHOD: The study used a cross-sectional study on 155 respondents at X Hospital in West Jakarta. Pelvic Girdle Pain assessed using the Pelvic Girdle Questionnaire. Data analysis was performed using the chi-square test. RESULT: This study showed that 28.4% have Pelvic Girdle Pain, there were no significant relationship between age, education level, parity, pregnancy interval and Pelvic Girdle Pain in pregnant women. (p=0.175; p=0.543; p=0.476; p=0.296). As for the body mass index, gestational age, and sport activity showed a significant relationship with Pelvic Girdle Pain in pregnant women. (p=0.000; p=0.000; p=0.001). CONCLUSION: There is significant relationship between body mass index, gestational age, and physical activity with pelvic girdle pain in pregnant women. There is no significant relationship between age, education level, parity, and pregnancy interval with pelvic girdle pain in pregnant women.